IMPLEMENTASI MEDIA PEMBELAJARAN MATEMATIKA BERNUANSA ISLAMI SEBAGAI SARANA PENGUATAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 LUHAK NAN DUO - Dodi Akbar; Darul Ihsan; Awaludin Hasibuan; Ismail Syakban (STKIP Pesisir Selatan, 2025)
Objective: This study aims to examine critically the implementation of Islamic-nuanced mathematics learning media as a means of strengthening Islamic Religious Education (PAI) values at SMP Negeri 1 Luhak Nan Duo. Methods: This research employed a qualitative descriptive approach with a case study design. Data were collected through classroom observations, in-depth interviews with mathematics teachers and students, and documentation analysis of lesson plans and learning media. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. Results: The findings reveal that the implementation of Islamic-nuanced mathematics learning media has not been carried out optimally. The integration of Islamic values tends to be incidental, not systematically planned, and largely depends on individual teacher initiatives. Limitations in teachers’ competencies, time constraints, and the absence of specific school policies hinder the effective use of such media in strengthening PAI values. Novelty: This study provides a critical insight into the managerial gaps in integrating Islamic values through mathematics learning media in public junior high schools, highlighting the need for systematic management support rather than solely pedagogical efforts.